2022
DOI: 10.26656/fr.2017.6(1).206
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of two Thai pigmented rice cultivars against H2O2-induced oxidative damage in HT-29 cell culture

Abstract: Radicals derived from exogenous and endogenous sources are considered to be the principal cause of genetic damage. Exogenous and endogenous radicals participate in the reactive oxygen species (ROS) formation, which leads to damages in the DNA, RNA, proteins and lipids. However, dietary compounds, mainly from pigmented rice, are an essential source of antioxidants that help protect cells from damage. This study seeks to determine the antioxidant properties and cytoprotective effect of two Thai pigmented rice ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Black rice extracts demonstrate a protective effect against TBHP-induced oxidative stress in HepG2 cells [16]. A previous study also reported that glutinous black rice at a concentration of 0.31 -2.5 mg/mL against oxidative stress caused by H2O2 on HT-29 cells showed a cytoprotective effect [17]. In line with the previously reported cytoprotective effect of EBRB 'Sembada Hitam' on NIH3T3 cells exposed to hydrogen peroxide (H2O2), which showed significant protection at concentrations starting from 7.81 mg/mL [18], this study aims to investigate the protective effect of EBRB 'Sembada Hitam' on Vero cells against H2O2-induced toxicity.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Black rice extracts demonstrate a protective effect against TBHP-induced oxidative stress in HepG2 cells [16]. A previous study also reported that glutinous black rice at a concentration of 0.31 -2.5 mg/mL against oxidative stress caused by H2O2 on HT-29 cells showed a cytoprotective effect [17]. In line with the previously reported cytoprotective effect of EBRB 'Sembada Hitam' on NIH3T3 cells exposed to hydrogen peroxide (H2O2), which showed significant protection at concentrations starting from 7.81 mg/mL [18], this study aims to investigate the protective effect of EBRB 'Sembada Hitam' on Vero cells against H2O2-induced toxicity.…”
Section: Introductionmentioning
confidence: 81%
“…Colored rice has a higher antioxidant activity than white rice and contains more phenolic compounds [47]. Previous studies reported that antioxidants from pigmented rice, including black rice [15][16][17]48] and red rice [17,48], can reduce the harmful effect of oxidative stress. We used one of the potentially natural ingredients in protecting cells affected by oxidative stress H2O2, which is black rice.…”
Section: Cytotoxicity Assay Ebrb 'Sembada Hitam' On Vero Cellsmentioning
confidence: 99%
“…There are several studies that have characterised plant extracts for their capacity to prevent oxidative stress damage in different cell lines, including those of large intestine (HT-29) and liver (HepG2). Thai pigmented rice extracts reduced ROS in HT-29 exposed to H 2 O 2 [ 42 ], though the efficacy varied depending on the type of rice used to obtain the extracts. In HepG2, cell extracts of Salvia officinalis and Thymus vulgaris reduced DNA damage induced after exposure to 300 µM of H 2 O 2 [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pa Ga Am Puen had the lowest antioxidant activity (Figure 6). Several studies have reported that pigmented rice is rich in phytochemicals, including flavonoid, -oryzanol, carotenoid, tocopherols, anthocyanins, and polyphenolic compounds, which play a role in antioxidants [21,69,71,76]. Ghasenzadeh et al [49] explained that 7 black rice cultivars, such as RB211, RB218, RB222, RB225, RB233, RB246, and RB248, showed the highest DPPH activity, followed by red and brown rice, which also had the lowest IC50 value, which contained the highest level of flavonoid and polyphenol compounds.…”
Section: Phytochemical Contentsmentioning
confidence: 99%
“…Black rice variety in Nepal had the highest total phenolic content and antioxidant activity [71]. Boonyanuphong and Tobgay [76] reported that the glutinous black rice showed higher total phenolic content, total flavonoid content, and anthocyanin content than the red rice, resulting in high antioxidant activity. On the other hand, the present study showed that the highest antioxidant activity was observed in the red rice genotype, namely Mali Daeng, and Nieng Guang.…”
Section: Phytochemical Contentsmentioning
confidence: 99%